Աբրահամ արք. Քիւբէլեան-Եկէնեանի անտիպ ժամանակագրութիւնն ու պատմական գրառումները (1816-1829) - Մինասյան, Միհրան («Նաիրի» հրատ.)
Apraham Archbishop Koupelian-Yegenian (Kilis 1786 – Aleppo 1832), the prelate of the Armenian Catholic community, was a poet, translator, and author of religious books. He wrote equally well in Armenian and Arabic. Of special historic importance is his detailed diary about the one-hundred-and-one days of the Aleppo revolt from 1819-1820; it was published in Arabic in a single volume in Aleppo in 2008. This publication (with an introduction and detailed annotations) contains a previously unpublished chronography and notes on the history of Aleppo written by Archbishop Koupelian and found in his notebook (which is kept in the archive of the Armenian Catholic prelacy in Aleppo). This chronographic work includes information from different regions, as well as eyewitness and auricular witness accounts; he himself was part (or had witnessed some) of these events. Архиепископ Абраам Кюпелян (Килис 1786 – Алеппо 1832), глава армянской католической общины Алеппо, был поэтом, переводчиком и автором религиозных книг. Он писал как на армянском,так и на арабском языке. Особо ценен его подробный дневник народного восстания в Алеппо в 1819-1820 гг., длившегося сто один день, изданный на арабском отдельной книгой в Алеппо в 2008 г. Настоящая публикация, снабженная предисловием и подробным комментарием, представляет Хронику и относящиеся к истории Алеппо записи архиепископа Кюбеляна, найденные в его записной книжке, хранящейся в архиве армянского католического прелатства в Алеппо. Эти записки хронологического характера включают известия из различных мест, свидетельства очевидцев и участников событий, среди которых часто оказывался он сам. События, представленные в Хронике, имеют обширную географию: хотя главным местом их действия является Алеппо, однако есть также сведения из Константинополя, Сиса, Бейрута, Айнтапа, европейских стран и т.д.
Keywords: Հրապարակումներ; Բանասիրություն